Impact of Progerin Expression on Adipogenesis in Hutchinson—Gilford Progeria Skin-Derived Precursor Cells - Farah Najdi (Cells, 2021)
Hutchinson–Gilford progeria syndrome (HGPS) is a segmental premature aging disease caused by a mutation in LMNA. The mutation generates a truncated and farnesylated form of prelamin A, called progerin. Affected individuals develop several features of normal aging, including lipodystrophy caused by the loss of general subcutaneous fat. To determine whether premature cellular senescence is responsible for the altered adipogenesis in patients with HGPS, we evaluated the differentiation of HGPS skin-derived precursor stem cells (SKPs) into adipocytes. The SKPs were isolated from primary human HGPS and normal fibroblast cultures, with senescence of 5 and 30%. We observed that the presence of high numbers of senescent cells reduced SKPs’ adipogenic differentiation potential. Treatment with baricitinib, a JAK–STAT inhibitor, ameliorated the ability of HGPS SKPs to differentiate into adipocytes. Our findings suggest that the development of lipodystrophy in patients with HGPS may be associated with an increased rate of cellular senescence and chronic inflammation.